The impact of tourism in economic sustainability of protected areas - Mijalce Gjorgievski; Ace Milenkovski; Dejan Nakovski (UTMS Journal of Economics, 2017)
The national park Mavrovo has rich and diverse natural resources which are an important and valuable part of the area. In addition to the territory there are numerous attractive tourist landscapes and ambiental values which together with the cultural and historical heritage enrich the tourist offer of the park. The tourist values of the National Park have been enriched and completed with the numerous accommodations and related tourism infrastructure that has been built in order to meet the traveler's needs. According to the Spatial Plan of the Republic of Macedonia the National Park Mavrovo has a national and international tourist significance. Therefore, the authors consider it necessary to design a tourist development for the area which will improve the competitiveness of the demanding tourism market and to keep the importance of the region for the tourists. For this purpose, the authors made the projections by analysis which was made on the basis of the current situation in terms of tourism development and the basis of the concepts of sustainable tourism development. This approach should enable sustainable tourism management for the protected area and it will allow increased general economic development where tourism will be the main instigator.
Keywords: Q26; L83; 330; National Park; development; planning